Dry matter digestibility and metabolizable energy of crude glycerines originated from palm oil using fed rooster assay - Legawa, Astiari Tia; Wattanasit, Sutha; Wattanachant, Chaiyawan (Acta Scientiarum. Animal Sciences, 2017)
A study was conducted to determine the dry matter digestibility, gross energy (GE), the nitrogen-corrected apparent metabolizable energy (AMEn), and the nitrogen-corrected true metabolizable energy (TMEn) of two crude glycerine from two different sources. The first crude glycerine (CG1) was from a large scale biodiesel producer with high content of glycerol (89.49%) and low content of crude fat (1.73%), meanwhile the second crude glycerine (CG2) was from a medium scale biodiesel producer with lower content of glycerol than CG1 (38.36%) and high content of crude fat (23.63%). Fed rooster assay based on Sibbald (1976) was used in the experiment. The experimental feed consisted of ground corn and three levels of crude glycerine (0, 10, and 20%). Twenty four Hisex brown roosters were housed in metabolic cages. Roosters were force fed with 30 g experimental feed, after 24 hours of fasting. Excreta collection was performed for two days while the roosters were fasting again. The content values of GE, AMEn, and TMEn of CG1 were 4065.18, 2926.59, and 3068.73 kcal kg-1 and for CG2 were 5928.09, 4010.11, and 4054.52 kcal kg, respectively.